The Symbolic Meaning of Nâshiyah Kâdzibah in Q.S. al-‘Alaq/96 Verse 16: A Study of Qur’anic Exegesis and Neuroscience - Chaniago, Rendy Iskandar; Kerwanto, Kerwanto (Abdurrauf Journal of Islamic Studies, 2025)
This article examines the symbolic meaning of the phrase nâshiyah kâdzibah khâthi’ah in Q.S. al-‘Alaq verse 16 through an integrative approach combining tafsir studies and neuroscientific perspectives. The phrase is often translated as “a lying and sinful forelock,” yet a literal interpretation does not sufficiently capture the depth of its moral and psychological messages. This study aims to explore the symbolic dimension of the verse by connecting it to the neurological function of the frontal lobe as the center of human behavioral control. The research adopts a qualitative methodology using a library research design, with data analyzed descriptively through in-depth textual analysis of primary literature in Qur’anic exegesis and neuroscience. Key sources include Tafsir al-Qur’an al-‘Azh?m by Ibn Kathir, F? Zhil?l al-Qur’an by Sayyid Qutb, Tafsir al-Misbah by Quraish Shihab, and Tafsir al-Aayaat al-Kauniyah by Zaghlul al-Najjar. The findings reveal that the Qur’an symbolically refers to the human brain region responsible for moral judgment, behavior regulation, and decision-making—known in modern neuroscience as the frontal lobe. This study highlights the relevance of Qur'anic symbolic expression in dialogue with contemporary scientific discoveries. [Artikel ini menelaah makna simbolik frasa nâshiyah kâdzibah khâthi’ah dalam Q.S. al-‘Alaq ayat 16 melalui pendekatan tafsir dan neuroscientific. Frasa ini sering diterjemahkan sebagai “ubun-ubun pendusta dan durhaka”, namun pemahaman literal tidak sepenuhnya mencerminkan kedalaman pesan moral dan psikologis yang terkandung di dalamnya. Tujuan penelitian ini adalah untuk mengungkap makna simbolik dari frasa tersebut dengan mengaitkannya pada fungsi neurologis lobus frontal sebagai pusat kendali perilaku manusia. Penelitian ini menggunakan metode kualitatif dengan jenis penelitian kepustakaan (library research), yang dianalisis secara deskriptif melalui teknik analisis mendalam terhadap literatur utama bidang tafsir dan neurosains. Sumber data mencakup kitab-kitab tafsir klasik dan kontemporer seperti Tafsir Al-Qur’an Al-‘Azhîm karya Ibnu Katsir, Fî Zhilal Al-Qur’an karya Sayyid Qutb, Tafsir Al-Misbah karya Quraish Shihab, serta Tafsir Al-Aayaat Al-Kauniyah karya Zaghlul An-Najjar. Hasil kajian menunjukkan bahwa Al-Qur’an secara simbolik telah merujuk pada bagian otak manusia yang mengatur aspek moral, perilaku, dan pengambilan keputusan, yang dalam ilmu neurosains modern dikenal sebagai lobus frontal. Simpulan ini memperlihatkan relevansi antara pesan wahyu dan temuan sains kontemporer.]